Duodenal varices successfully treated with cyanoacrylate injection therapy. (25th May 2011) - Malik, Ahsan; Junglee, Naushad; Khan, Anwar; Sutton, Jonathon; Gasem, Jaber; Ahmed, Waqar
Abstract : Duodenal varices are a rare complication of portal hypertension secondary to liver cirrhosis. Compared to oesophageal varices, they bleed less often but are also more difficult to diagnose and treat. There is no established treatment for bleeding duodenal varices and different treatment strategies have been employed with variable results. The authors present a case of 52-year-old male who was admitted with melaena. Upper gastrointestinal endoscopy was performed which identified bleeding varices in the second part of duodenum. The varices were injected with cyanoacrylate and the outcome was favourable. Subsequent endoscopies showed complete resolution of the varices. The authors conclude that cyanoacrylate injection is an effective first-line treatment for bleeding duodenal varices.